Optimization of the process parameters for extruded commercial sinking fish feed with mixed plant protein sources. (28th November 2020) - Wang, Hao; Ma, Shifeng; Yang, Jie; Qin, Yuchang; Cheng, Hongyuan; Xue, Min; Li, Jun; Li, Junguo
Abstract: The aim of the investigation was to optimize extrusion process parameters for processing commercial sinking fish feed with mixed plant protein sources in a pilot‐scale twin‐screw extruder equipped with a preconditioner. It has been found out that the bulk density of feed pellets increased with the moisture content in the range of 22–27% (wt), then decreased with the moisture content from 27 to 32%. Meanwhile, increasing moisture content (22–32%) resulted in a decrease of pellet hardness, water solubility, and specific mechanical energy (SME), and an increase of pellet hydration time. There was a significant decrease ( p <.05) in SME, bulk density, and hydration time when the die temperature was increased from 90 to 140°C. Increasing the screw speed (180–300 rpm) led to an increase in SME, water solubility index (WSI), and water solubility, but a decrease of water solubility index (WAI). The optimal process parameters for processing the sinking feed pellets were moisture content: 26.6%, screw speed: 180 rpm, and die temperature: 113°C. These operation parameters provide a reference for the industrial production of fish feed with mixed plant protein sources. Practical applications: In recent years, plant protein has been increasingly developed as an aquatic feed source, but this has resulted in quality fluctuations for fish feed pellets. Sinking pellets require sufficient gelatinization but should avoid floating due to excessive swelling. Thus, it is important to control the parameters of the extrusion process during sinking feed production. Contrary to conventional laboratory studies, this study used a pilot extrusion line (capacity: 70–150 kg/hr) equipped with a steam adding preconditioner and an automatic data acquisition system for parameter optimization. Moreover, we defined satisfactory products through the targeted evaluation of key indicators such as water solubility and hydration time. The results of this study provide a reference for the industrial production of sinking feed with mixed plant proteins. Abstract :